EFEK DEFLEKSI PADA SUDU TURBIN ANGIN TERHADAP KELUARAN DAYA - Atmadi, Sulistyo; Fitroh, Ahmad Jamaludin (Indonesian Journal of Aerospace, 2006)
The type of material used in the fabrication of wind turbine blade is a very important factor so that it will not exceed the allowable maximum deflection. An analysis is conducted to study this deflection effect to that power output and as case study, a 7.6 m blade of 10 kW LPN 10000 E turbine is used. Several assumption as such as deflection due to wind speed at perpendicular to local plane local blade are diameter blade and direction of aerodynamic at aerofoil plane local blade are considered. The distribution of blade deflection along the twisted span is assumed uniform. Calculation is performed for the polynomial order of 2,3 and 4, with variety of deflection of 0.2 m, 0.5m, 1 m and 1.5 m. for design wind speed of 9 m per s it was found that for 0.5 deflection, the losses of 6 percent, 9 percent and 12 percent for blade shape polynomial order 2,3 and 4 consequentively are produced; whereas for 1.5 m deflection, losses are 46 percent, 53 percent, and 56 percent for the same polynomial shape. If a maximum loss of 10 percent is taken, then the max allowable deflection is 0.5 m.